(3JSYjfjGJ GdGbJUGO GdLRGFQjs - (3YHO GdeLjO(B, (3HhRjOjs ((3GdLRGFQ(B:s (3ehae ddfTQ(B,s, 1999)
(3GdJUNe heTcdI ejRGf GdeOahYGJ (B-(3GUdGM GdbWGY GdYehej hGdNhUUI (B-(3GbJUGO GdShb hGdJaJM GdGbJUGOj (B-(3GdHWGdI hGdabQ (B- (3OhdI ,GbJUGO GdShb ,OjebQGWjI SjGSI (B-(3YhdeI GdGbJUGOs
Keywords: (3GdEbJUGO(B- (3GdLRGFQs; (3GdbWGY GdYGes